Effective Municipal Governance: Evaluating the Role of the Municipal Public Accounts Committee in the Cape Winelands District Municipality - Matthyse, Magon Rensia (Stellenbosch : Stellenbosch University, 2026)
Thesis (MPA)--Stellenbosch University, 2026.